2016
DOI: 10.1111/fare.12173
|View full text |Cite
|
Sign up to set email alerts
|

Family Relations, Stress, and Vulnerability: Biobehavioral Implications for Prevention and Practice

Abstract: Developmental psychobiology research supports the hypothesis that individual differences in biological stress systems that are sensitive to environmental experiences are associated with individual adjustment problems. Negative social experiences, especially in family contexts, contribute to the dysregulation of set‐points and thresholds of biological stress reactivity that affects long‐term adaptation and adjustment. The goal of this review is to discuss the current findings on how negative parent–child relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 97 publications
3
28
0
1
Order By: Relevance
“…Factors such as gender, social status, and social connections or networks will influence the extent to which students get bullied; Further, non-supportive family or companion, as well as intense roommate relationship also contribute to PhD stress. These results also corroborate findings that negative family relationships can cause stress, impact mental health and even cause a mental illness to worsen (e.g., Ha & Granger, 2016;Jang, Zippay, & Park, 2012). Our data also reveal that stress is more prominent among female students, corroborating with previous research findings (e.g., Gu, Levin, & Luo, 2017;Morse & Dravo, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Factors such as gender, social status, and social connections or networks will influence the extent to which students get bullied; Further, non-supportive family or companion, as well as intense roommate relationship also contribute to PhD stress. These results also corroborate findings that negative family relationships can cause stress, impact mental health and even cause a mental illness to worsen (e.g., Ha & Granger, 2016;Jang, Zippay, & Park, 2012). Our data also reveal that stress is more prominent among female students, corroborating with previous research findings (e.g., Gu, Levin, & Luo, 2017;Morse & Dravo, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Other prevention research on behavioral parent‐training programs found parental reductions of stress among those caring for children with developmental disabilities (Lindo, Kliemann, Combes, & Frank, ). These studies suggest that the positive effects of parenting interventions may spill over to the biological systems of individuals (Ha & Granger, ).…”
Section: The Cascading Resilience Modelmentioning
confidence: 99%
“…Using cross-lag models could be an important way to test some of these ideas (e.g., Burt, Obradović, Long, & Masten, 2008). Dynamic systems theorists have measured micropatterns with state space grids (Granic & Hollenstein, 2003;Ha & Granger, 2016), which can map both negative and positive interactions over time. Also, social networking methods may elucidate ways that positive cascades spread in communities (Osgood et al, 2013).…”
Section: Longitudinal Researchmentioning
confidence: 99%
“…Attention to children's attachment is essential for improving outcomes for children with early adversities that have resulted in disrupted relationships, such as placement in foster care (Mennen & O'Keefe, ). Furthermore, there is evidence that children's biological stress response systems are malleable and that interventions focused on improving parenting and family relationships can normalize the child's physiological response to stress (Ha & Granger, ).…”
Section: Current Approaches To Reducing the Impact Of Adverse Early Ementioning
confidence: 99%